2016
DOI: 10.1371/journal.pone.0160951
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Active Subunit of Nitrogenase via Integration into Plant Organelle Genome

Abstract: Nitrogen availability is crucial for crop yield with nitrogen fertilizer accounting for a large percentage of farmers’ expenses. However, an untimely or excessive application of fertilizer can increase risks of negative environmental effects. These factors, along with the environmental and energy costs of synthesizing nitrogen fertilizer, led us to seek out novel biotechnology-driven approaches to supply nitrogen to plants. The strategy we focused on involves transgenic expression of nitrogenase, a bacterial m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
69
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 44 publications
2
69
0
2
Order By: Relevance
“…In plant chloroplasts ex vivo Fe protein activity required the lowering of ambient oxygen conditions (Ivleva et al, 2016). By contrast, aerobically grown yeast expressing matrix targeted NifH and NifM were capable of producing a functional Fe protein (López-Torrejón et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In plant chloroplasts ex vivo Fe protein activity required the lowering of ambient oxygen conditions (Ivleva et al, 2016). By contrast, aerobically grown yeast expressing matrix targeted NifH and NifM were capable of producing a functional Fe protein (López-Torrejón et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…1), such as those required for iron-sulfur cluster assembly, could also be considered. Two recent studies have shown that the [Fe-S] cluster biosynthesis components from eukaryotic organelles can substitute for NifU and NifS to incorporate the [4Fe-4S] cluster into the Fe protein of nitrogenase (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested chloroplasts, root plastids, or mitochondria as suitable locations for expression of nitrogenase in eukaryotes (18)(19)(20). These energy-conversion organelles can potentially provide reducing power and ATP required for the nitrogen-fixation process.…”
mentioning
confidence: 99%
“…In recent studies it has been shown that an active dinitrogenase reducatase can be produced in eukaryotes, provided it is targeted to either mitochondria in yeast or plastids in tobacco (12,13). These achievements are noteworthy for two reasons.…”
mentioning
confidence: 99%
“…However, neither NifU nor NifS is necessary for the production of an active nitrogenase reductase in either yeast or tobacco (12,13), indicating that counterparts involved in assembly of iron-sulfur cofactors in eukaryotic organisms-for example Isu and Nfs1 (15)-can substitute for the nitrogen-fixation-specific assembly components. It should be noted that NifU and NifS also supply the iron-sulfur building blocks necessary for formation of the complex cofactors associated with dinitrogenase (Fig.…”
mentioning
confidence: 99%